Nano-Biosensors for Detection and Monitoring - Kant, Krishna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Young readers will find the Reprint useful for learning about the systematic study and review of the many themes in the area of microfluidic-based biosensing. Empirical research and comprehensive reviews regarding the use of microfluidic technology in biosensing and point-of-care system development are included in this Reprint.